Outcome of Acute Kidney Injury in Sudanese Children — An Experience from a Sub-Saharan African Unit. Issue 5 (July 2014) - Abdelraheem, Mohamed; Ali, El-Tigani; Osman, Rania; Ellidir, Rashid; Bushara, Amna; Hussein, Rasha; Elgailany, Shiraz; Bakhit, Yassir; Karrar, Mohamed; Watson, Alan; Abu-Aisha, Hasan
Background: Acute Kidney Injury (AKI) is an important cause of morbidity and mortality in developing countries. Although continuous renal replacement therapy is gaining more popularity worldwide, peritoneal dialysis (PD) in children remains an appropriate therapy for AKI in children for all age groups including neonates. Methodology: We retrospectively reviewed all children who have been admitted with AKI at the pediatric nephrology unit, Soba University Hospital, Khartoum, during the period from January 2005 to December 2011. Results: Over 7 years we recorded 659 children of whom 362 (54.9%) were male. The spectrum of age was variable with the majority being neonates, 178 (27.1%). The average patient admission rate was 94 patients per year, with an estimated incidence of 9.8 patients/million population/year. Common causes of AKI were sepsis 202 (30.8%), acute glomerulonephritis 75 (11.5%) and obstructive uropathy due to stones 56 (8.5%). The most common dialysis modality used was PD, 343 (52.4%), and peritonitis was reported in 53 (15.4%) patients. Recovery from AKI was achieved in 450 (68.9%) children, 37 (5.7%) went into chronic kidney disease (CKD), 33 (5.1%) referred to the pediatric surgery and 194 (29.7%) died. Conclusion: In the setting of developing countries where AKI is a common cause of morbidity and mortality, reasonably equipped renal units with adequately trained medical staff may save many lives. International funding programs for communicable diseases and charity organizations should include AKI management in their programs. Acute PD remains the treatment modality of choice for AKI in developing countries.